Advanced Engineering Schools: Transfer of Competencies and Innovations in the Interests of Regional and Sectoral Development - A. V. Keller; A. V. Suvorov; S. S. Shadrin; I. A. Korshunov; N. N. Shirkova (Высшее образование в России)
The creation of advanced engineering schools at universities to improve the quality of human capital is becoming increasingly relevant. This paper examines the relationship between the development of economics, engineering education, the results of intellectual activity and the scale of launching new educational programs in universities.The analysis demonstrates that activities in the field of engineering education will develop in the interests of knowledge transfer in areas of technological sovereignty with large amounts of investment. However, so far, the educational activity of advanced engineering schools correlates with the level of development of industries in the regions, which creates challenges and opportunities for expanding cooperation and introducing technologies beyond their borders throughout the industry.The study shows that the scale of launching new educational programs is interconnected with the general culture of research and the creation of professional education programs at the university. The high potential of research activities, in general, is a prerequisite for the development and implementation of engineering educational programs in demand in the real sector. At the same time, the results of scientific and intellectual activity are often the source of their creation. The high level of launching additional professional education programs at the university makes it possible to expand the involvement of university teams in the development and implementation of educational programs and engineering orientation.The authors offer practical recommendations aimed at further development of engineering education for both students in educational institutions and current specialists in the interests of ensuring the technological sovereignty of the Russian Federation, the development of the university’s third mission, as well as to stimulate sales of educational programs, innovative solutions and projects.